La lettura del paesaggio come strumento di turismo culturale - Bradley, Frederick (Ri-Vista. Research for landscape architecture, 2015)
The GUIPA project, Guide al Paesaggio d’Italia is going on since 2004 with the goal to develop a specific editorial space. It intends to spread the landscape diversities of Italy by a sequence of lectures based on scientific informations. Development of a cultural tourism, expression of a diffuse knowledge about character and dynamics of Italian landscapes, could be an important cultural inducement in their protection and management. The project is developing, with new guides, which are increasing its covering of italian territory, and with new modality of enjoyment